Effective outcomes of home-based unsupervised rehabilitation protocol after rotator cuff repair: a prospective study - Khatua, Jugaratna; Baskey, Somnath; Nayak, Manmatha; Patra, Gopabandhu (International Journal of Research in Orthopaedics, 2025)
Background: Rotator cuff tears, common in both elderly and athletic populations, require effective rehabilitation following surgical repair for optimal recovery. The study evaluates the outcomes of a patient-led home-based rehabilitation program after rotator cuff repair. Methods: This prospective study was conducted at SCB Medical College and Hospital, Cuttack, with 46 patients who underwent rotator cuff repair via mini-open incision. A structured home-based rehabilitation program was followed, with outcomes assessed at one year using visual analogue scale (VAS), disabilities of the arm, shoulder, and hand (DASH) score, range of motion, and cuff strength. Results: Postoperative VAS score improved from 7.3 to 1.5, and the DASH score decreased from 35.0 to 5.2. Range of motion significantly improved in active abduction, forward flexion, and external rotation. Ninety-one percent of patients returned to work within three months, though five failures were noted, including one with stiffness and four with retear. Conclusions: The home-based rehabilitation program resulted in significant pain relief and functional recovery, with a high return-to-work rate. The study suggests that home-based rehabilitation is a viable alternative to supervised physiotherapy.